Taekwondo anaerobic intermittent kick test: Discriminant validity and an update with the Gold-Standard Wingate Test - Tayech, A.; Arbi Mejri, M.; Chaouachi, M.; Chaabene, H.; Hambli, M.; Brughelli, M.; Behm, D. G.; Chaouachi, A. (Journal of Human Kinetics, 2020)
The aim of this study was to update the validity of the Taekwondo Anaerobic Intermittent Kick Test compared with the 30-s Wingate anaerobic test as the "Gold-Standard", squat jump and countermovement jump tests. The second objective was to examine whether this new specific test would be able to effectively discriminate between elite taekwondo athletes of different competitive levels. Twenty taekwondo athletes (15 males and 5 females) participated in the validation component, whereas 18 (14 males and 4 females) and 16 (13 males and 3 females) athletes participated in the reliability analysis of the Wingate anaerobic test and jumping tests, respectively. They performed these tests on two separate occasions (i.e., test-retest), in addition to the Taekwondo Anaerobic Intermittent Kick Test. To establish test`s discriminatory capability (i.e., construct validity), two subgroups were identified based on their international and national taekwondo performance: 10 elite (8 males and 2 females) and 9 sub-elite (7 males and 2 females) athletes. Wingate anaerobic test and jumping tests performances showed excellent reliability (ICC > 0.90, SEM < 5% for most variables). Significant correlations between Taekwondo Anaerobic Intermittent Kick Test, Wingate anaerobic test, and jumping tests` variables were mostly "large". Elite taekwondo athletes showed greater taekwondo test performances compared with their sub-elite counterparts (p < 0.001). Receiving operating characteristic analysis indicated that the taekwondo specific test was able to effectively discriminate between elite and sub-elite taekwondo athletes. Overall, the findings of the current study support the concurrent validity of the Taekwondo Anaerobic Intermittent Kick Test. In particular, the Taekwondo Anaerobic Intermittent Kick Test showed good ability to effectively discriminate between taekwondo athletes of different competitive levels.